2000
DOI: 10.1046/j.1365-2036.2000.00706.x
|View full text |Cite
|
Sign up to set email alerts
|

Cure of Helicobacter pylori infection does not improve symptoms in non‐ulcer dyspepsia patients—a double‐blind placebo‐controlled study

Abstract: Although histological parameters were significantly improved in the treatment group, there was no significant improvement in symptoms of NUD in the treatment group compared to placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
92
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(94 citation statements)
references
References 28 publications
2
92
0
Order By: Relevance
“…Though, meta-analyses [12,13] has already concluded H. pylori treatment was succeed in halting progression of PL, we believe the retrospective design and inconsistent definitions of PL progression utilized might have a large extent influence to the pooled results. This is why most of previous RCTs assigned a single pathologist to evaluate the individual histological changes before and after eradication [1,2,31,34,37,38].Therefore, to make a more reliable investigation, we performed an analysis only included RCTs with individual histological change provided and further conducted subgroup analyses based on the definition of PL progression (histological step or histological score).In our results, the halt effect was more obviously observed in studies applied histological score comparison with studies compared histological step. Additional, in studies used a histological step comparison, eradication seems to promote the deterioration in those with a baseline diagnosis CIM.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Though, meta-analyses [12,13] has already concluded H. pylori treatment was succeed in halting progression of PL, we believe the retrospective design and inconsistent definitions of PL progression utilized might have a large extent influence to the pooled results. This is why most of previous RCTs assigned a single pathologist to evaluate the individual histological changes before and after eradication [1,2,31,34,37,38].Therefore, to make a more reliable investigation, we performed an analysis only included RCTs with individual histological change provided and further conducted subgroup analyses based on the definition of PL progression (histological step or histological score).In our results, the halt effect was more obviously observed in studies applied histological score comparison with studies compared histological step. Additional, in studies used a histological step comparison, eradication seems to promote the deterioration in those with a baseline diagnosis CIM.…”
Section: Discussionmentioning
confidence: 83%
“…Prospective studies, especially RCTs, which regarded the occurrence of GC as primary outcome were few, because the gastric carcinogenesis was time-consuming process which need long-term follow-up. Instead, based on the theory of consecutive progression process, many prospective studies evaluated the effect of H. pylori treatment in the PL to indirectly reflect the GC preventive effect [2,[29][30][31][32][33][34][35][36]. Though, meta-analyses [12,13] has already concluded H. pylori treatment was succeed in halting progression of PL, we believe the retrospective design and inconsistent definitions of PL progression utilized might have a large extent influence to the pooled results.…”
Section: Discussionmentioning
confidence: 99%
“…Agents with property of opioid agonists or serotonin type-3 receptor antagonists are considered to diminish visceral hypersensitivity, and Helicobacter pylori infection eradication therapy has also been considered, although the usefulness of these therapies has not been confirmed and mostly a combination of above is required to tackle the condition [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…This trial evaluated 84 patients and reported no change in mean dyspepsia score between those randomised to H. pylori eradication therapy and placebo. Nine trials, 207,208,210,212,214,[216][217][218][219] evaluating a total of 2541 patients, reported dyspepsia as a dichotomous outcome at 6 months or 1 year (Figure 18 ). Three trials 207,208,212 reported continuous data for 848 patients at 1 year ( Figure 19 ).…”
Section: Results Of the Review The Effect Of H Pylori Eradication Onmentioning
confidence: 99%